Simulating Pollution from Na Duong I&II Cluster of Thermal Power Plants to Ambient Air Quality - Duong Ngoc, Bach (VNU Journal of Science: Earth and Environmental Sciences, 2017)
The article presents some results of applying AERMOD VIEW 8.2 software to simulate pollutant dispersions of TSP, SO 2 and NO 2 from the chimneys of Na Dương I&II cluster of thermal power plants, Lang Son province. Research result shows that in the condition of normal operation (as designed) of plant’s electrostatic dust filter system, the hourly average concentration of TSP around this area is relatively high and nearly reaches the allowable threshold of current standard (TSP concentration is approximately 77.8% of the allowable threshold value). In the case of an accident (the electrostatic dust filter system stops working), the most affected areas by the pollution are the agricultural lands and the production forest lands surrounding the site, where the highest hourly average concentration of TSP is 2841 µg/m 3 , 9 times higher than the standard (QCVN 05-2013-BTNMT; hourly average TSP: 300µg/m 3 ).